Status wspólnika spółki handlowej jako tytuł ubezpieczenia społecznego - Tomanek, Artur (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The author analyses the status of a partner in a commercial partnership in the light of the scope of a statutory social security scheme. The text shows that a legislator has no clear idea of the legal regulation. The scope of compulsory social insurance should be corrected in respect of the partners in a limited partnership and private partnership unlimited with share capital. The status of the partner treated as a basis of compulsory social insurance should depend on whether apartnership or a company actually carries out economic activity. In the author’s opinion there is no need for social insurance of the capital. Therefore the compulsory social insurance of the partners in joint stock companies may be accepted only by way of exception.
Keywords: statutory social security scheme; compulsory insurance; commercial partnership; joint stock company; partner; economic activity